2012
DOI: 10.1099/ijs.0.033787-0
|View full text |Cite
|
Sign up to set email alerts
|

Description of Verrucosispora qiuiae sp. nov., isolated from mangrove swamp sediment, and emended description of the genus Verrucosispora

Abstract: A Micromonospora -like strain, RtIII47T, was isolated from a mangrove swamp in Sanya, Hainan Province, China. Phylogenetic analysis based on the 16S rRNA gene sequence indicated that the strain had a close association with the genus Verrucosispora and shared the highest sequence similarity with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…The results of the present study confirm and extend those reported by Fiedler et al (2008) in showing that the proximicin-producing strain MG-37 T has chemotaxonomic, molecular and morphological properties in line with its classification in the genus Verrucosispora (Rheims et al 1998;Goodfellow et al 2012;Xi et al 2012 The description is based on data taken from this and an earlier study ).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The results of the present study confirm and extend those reported by Fiedler et al (2008) in showing that the proximicin-producing strain MG-37 T has chemotaxonomic, molecular and morphological properties in line with its classification in the genus Verrucosispora (Rheims et al 1998;Goodfellow et al 2012;Xi et al 2012 The description is based on data taken from this and an earlier study ).…”
Section: Discussionsupporting
confidence: 91%
“…The isolate was examined for chemotaxonomic and morphological properties characteristic for the genus Verrucosispora (Goodfellow et al 2012;Xi et al 2012). The arrangement of hyphae and spores were examined on an oatmeal agar (ISP medium 3; Shirling and Gottlieb 1966) plate which had been incubated at 28 o C for 2 weeks.…”
Section: Chemotaxonomy and Morphologymentioning
confidence: 99%
See 3 more Smart Citations